Enhancing the wheat growth through micronutrients enriched biochar under salt stress - Mukhtar, Muhammad Salman; Khan, Waqas-ud-Din; Khan, Amin U.; Rahman, Shafeeq Ur; Guo, Wei (Frontiers in Sustainable Food Systems, 2023)
Crop irrigation with brackish water having high Na+ is a common practice in developing countries like Pakistan; hence increasing the saline-sodic soils throughout the region. Therefore, two independent studies were conducted to evaluate the impact of minerals enriched contrasting biochars (MECBs) in mitigating Na+ toxicity on soil physicochemical properties, wheat growth, and physiology. In 1st trial, an incubation experiment was conducted having 32 treatments including simple biochar (SBc), manganese enriched biochar (MnBc), zinc enriched biochar (ZnBc), and iron enriched biochar (FeBc) applied at two rates (0.1% and 0.5%) with four different salinity levels such as 10, 20, 30, and 40 dSm−1. The soil was sampled after the 8th, 16th, and 24th day of incubation. Among the four sources of biochar, MnBc (0.1%) + 40 dSm−1 and FeBc (0.5%) + 40 dSm−1 showed efficient results to tolerate salinity stress in soil by efficiently reducing the availability of Na+ (60% and 30%) when compared to SBc (0.5%) + 40 dSm−1. Then, a pot study was conducted with 20 different treatments (control, SBc, MnBc, ZnBc, and FeBc) at four different salinity levels, i.e., 0, 5, 10, and 15 dSm−1. There were four replicates and the crop was harvested after 60 days of germination. The application of brackish water (control+15 dSm−1) significantly reduced the fresh weight of root (28%) and shoot (34%) of wheat (Triticum aestivum L.) as compared to FeBc+15 dSm−1. However, the soil Na+ toxicity was significantly decreased (23%) by the application of FeBc+15 dSm−1 as compared to control+15 dSm−1. Similarly, a significant increase was observed in leaf chl. a, b and photosynthetic rate (75%, 3 and 2-folds); however, a significant decrease was observed in transpiration rate (50%) in T. aestivum L. treated with FeBc+15 dSm−1 as compared to control+15 dSm−1. Interestingly, FeBc+15 dSm−1 also played a vital role to prevent oxidative damage by controlling the shoot CMP (63%) in T. aestivum L. by efficiently triggering the activities of shoot antioxidant enzymes such as APX (30%) and CAT (52%) when compared to control+15 dSm−1. In summary, it was evaluated that FeBc showed the highest adsorption capacity of Na+ ions to regulate salinity stress by improving soil health and crop physiology.